Student Teams Achievement Division (STAD): Model pembelajaran cooperative learning dalam meningkatkan hasil passing bawah bolavoli - Riusman, Anggi (Edu Sportivo: Indonesian Journal of Physical Education, 2021)
The purpose of this study is to find out how much the increase in the application of the STAD cooperative learning model type to increase the results of passing down volleyball in class VIII5 students of SMPN 4 Siak Hulu. This research was conducted at SMPN 4 Siak Hulu. The variables used are under passing and cooperative learning model type STAD. The research subjects used were class VIII5 as many as 19 sons and 14 daughters in total 33 students. The data analysis technique used is descriptive statistics with the percentage. The results showed that the improvement of the basic techniques of passing under volleyball for grade VIII5 students of SMPN 4 Siak Hulu was good. The results obtained for the basic technique of passing under volleyball in grade VIII5 students of SMPN 4 Siak Hulu in cycle 1 were 66.6% “complete”, in cycle 2 experiencing an increase was 81.8% “completing”.